Evaluation of mechanical and metallurgical properties of submerged arc welded plate joint. (2021) - Rajkumar, T.; Prabakaran, M.P.; Arunkumar, G.; Parameshwaran, P.
Abstract: Submerged Arc Welding (SAW) is one of the major welding processes in industry because of its inherent advantages, including deep penetration and a smooth bead. In this study, mild steel (IS2062) 6 mm plates were welded by SAW process. The experiments were designed with three factors and three levels such as current, voltage and welding speed. Optimum process parameters were identified through Taguchi L9 orthogonal array and also studied the influence of SAW process parameters. Mechanical and metallurgical properties of the weld joint were investigated through Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Analysis (EDX). Microstructure of the weld zone resulting fine grains of pearlite and ferritic structure along with moderate precipitates were observed.